Christmas light flasher / Amiruddin Sollehhuddin - Sollehhuddin, Amiruddin (2002)
KEU 380 is one of the courses, which is totally different with other course. Here I need to produce a project. The project must be original and came from my own creativity. Like my university, I also have produce my project known as ‘CHRISTMAS LIGHT FLASHER’. This project is a straight-forward fixed pattern flasher for three sets of lights. However this is not usual 1-2-3 chasing pattern, this unit has six steps, 1, -1+2, -2, -2+3, -3, -3+1, and then repeated. If the three sets of lights are mixed on the tree, it is not that easy to see the pattern. On the prototype, the speed was fixed to about three steps per second, but it would be a simple matter to put a control pot on the front panel to set the mood if required. The triac outputs are driven from zero-crossing opto isolators, which virtually eliminate radio interference. The triacs are hard driven, making the outputs suitable for driving inductive loads such as the modern low voltage transformer driven Christmas light. The output can drive loads of up to 3 Amps (or possible even more if the PCB tracks are reinforced), making the unit suitable for driving higher powered outdoor lights. THIS PROJECT OPERATES FROM THE MAIN. MAINS VOLTAGE IS POTENTIALLY LETHAL. DO NOT CONSTRUCT IT UNLESS YOU ARE CERTAIN OF YOUR ABILITY TO DO SO SAFELY.